Immediate Initiation of Antiretroviral Therapy for HIV Infection Accelerates Bone Loss Relative to Deferring Therapy: Findings from the START Bone Mineral Density Substudy, a Randomized Trial. (26th June 2017) - Hoy, Jennifer F; Grund, Birgit; Roediger, Mollie; Schwartz, Ann V; Shepherd, John; Avihingsanon, Anchalee; Badal‐Faesen, Sharlaa; de Wit, Stephane; Jacoby, Simone; La Rosa, Alberto; Pujari, Sanjay; Schechter, Mauro; et al.
ABSTRACT: Both HIV infection and antiretroviral therapy (ART) are associated with lower bone mineral density (BMD) and increased fracture risk. Because the relative contributions of ART and untreated HIV to BMD loss are unclear, it is important to quantify the effect of ART on bone. We compared the effect of early ART initiation (CD4 >500 cells/μL) with deferred ART on change in BMD in the START Bone Mineral Density substudy, a randomized trial evaluating the effect of immediate ART initiation versus deferring ART (to CD4 <350 cells/μL). BMD was measured annually at the lumbar spine and hip by dual‐energy X‐ray absorptiometry (DXA). Percent change in BMD by treatment assignment (intent‐to‐treat analysis) was estimated using longitudinal mixed models and linear regression. Baseline and follow‐up DXA scans were available for 399 (195 immediate, 204 deferred) participants (median age 32 years, 80% non‐white, 26% women, median CD4 count 642 cells/μL). ART (most commonly including tenofovir and efavirenz) was used for 95% and 18% of follow‐up in the immediate and deferred ART groups, respectively. Through 2.2 years mean follow‐up, immediate ART resulted in greater BMD declines than deferred ART at the hip (–2.5% versus –1.0%; difference –1.5%, 95% confidence interval [CI] –2.2 to –0.8, p < 0.001) and spine (–1.9% versus –0.4%; difference –1.6%, 95% CI –2.2 to –1.0, p < 0.001). BMD declines were greatest in the first year of ART. In the immediate ART group, spine BMD stabilized after year 1, whereas hip BMD declined progressively over 2 years. After year 1, BMD changes were similar in the immediate and deferred groups. No clinical, HIV‐related, or ART characteristic predicted greater BMD loss in either group. All HIV treatment guidelines now recommend ART initiation at HIV diagnosis because of the reduced risk of serious clinical outcomes. Better understanding of the longer‐term consequences of the observed reductions in BMD is needed. Clinical Trials Registration: NCT00867048. © 2017 American Society for Bone and Mineral Research.